Agricultural Transformation and Inclusive Growth : The Malaysian Experience - World Bank Group (World Bank, Washington, DC, 2019)
The Malaysian story involves a farsighted leadership that has mobilized the considerable assets of a resource-rich country to translate a long-term vision of nation building into action and transformational results. This report analyzes what Malaysia did to achieve transformative results in agriculture. It focuses on four main areas in which the Malaysian experience is distinctive and which have been critical to its success, as follows: (1) The role of the public sector, encompassing national leadership, vision, and government action; (2) The main drivers of transformation and inclusive growth; (3) The role of value chains; (4) The inclusiveness of Malaysia's agricultural transformation.